GPS and injury prevention in professional soccer - Ehrmann, F. E.; Duncan, C. S.; Sindhusake, D.; Franzsen, W. N.; Greene, D. A. (The Journal of Strength and Conditioning Research, 2016)
This study investigated the relationship between GPS variables measured in training and gameplay and injury occurrences in professional soccer. Nineteen professional soccer players competing in the Australian Hyundai A-League were monitored for 1 entire season using 5 Hz Global Positioning System (GPS) units (SPI-Pro GPSports) in training sessions and preseason games. The measurements obtained were total distance, high-intensity running distance, very-high-intensity running distance, new body load, and meters per minute. Noncontact soft tissue injuries were documented throughout the season. Players' seasons were averaged over 1- and 4-week blocks according to when injuries occurred. These blocks were compared with each other and with players' seasonal averages. Players performed significantly higher meters per minute in the weeks preceding an injury compared with their seasonal averages (+9.6 and +7.4% for 1- and 4-week blocks, respectively) (p < 0.01), indicating an increase in training and gameplay intensity leading up to injuries. Furthermore, injury blocks showed significantly lower average new body load compared with seasonal averages (-15.4 and -9.0% for 1- and 4-week blocks, respectively) (p < 0.01 and p = 0.01). Periods of relative underpreparedness could potentially leave players unable to cope with intense bouts of high-intensity efforts during competitive matches. Although limited by Fédération Internationale de Football Association regulations, the results of this study isolated 2 variables predicting soft tissue injuries for coaches and sports scientists to consider when planning and monitoring training.